Ofloxacin-induced Fixed Drug Eruptions - Kushalkumar H. Gohel; Kusum V. Shah; Shivani Patel; Juliet Joy Joseph; Jilce Mathew (Journal of Integrated Health Sciences)
Fixed drug eruption (FDE) is a form of drug induced dermatosis condition. Drugs which most commonly induce FDE are antibiotics, anticonvulsants, antiviral agents and even nonsteroidal anti-inflammatory drugs. Here, we report a case of 50-year-old male with history of hepatosplenomegaly for which he was treated at a regional hospital and was prescribed with tablet ofloxacin (200 mg). The patient visited the pulmonary medicine department of our hospital for respiratory complaints and a dermatological reference was made for skin lesions. The findings concluded the case as a drug-induced FDE with pulmonary tuberculosis (TB). The offending drug (tablet ofloxacin) was withdrawn and suitable treatment was provided for FDE and pulmonary TB. One-month follow-up visit reported no fresh respiratory complaints and resolution of skin lesions. Based on this case report, it can be concluded that though FDE is not a common ADR of ofloxacin, caution must be addressed before prescribing it to the patient. For confirmed cases, it is essential to provide education and counseling to the patient and care giver to prevent its recurrence in future.